ANALISIS HUKUM TENTANG PERLINDUNGAN NASABAH PENYIMPAN DALAM LAYANAN INTERNET BANKING - Tita Nurdinna (LEGAL OPINION, 2025)
The author's conclusion is: Regulations regarding the legal protec-tion of customers using internet banking can be divided into two, namely preventive legal protection and repressive law. Legislation that directly regulates internet banking products does not yet exist, however, existing legislation already covers aspects of legal protec-tion of internet banking customers. Dispute resolution legal efforts are divided into two, namely: Non Litigation and Litigation. Non-litigation generally has several forms to resolve disputes, namely: Customer complaints, banking mediation, consumer dispute resolu-tion body (BPSK), arbitration and alternative dispute resolution (APS), this form of dispute resolution is carried out by parties who feel aggrieved or there is a difference of opinion either between indi-viduals, groups or between business entities. Meanwhile, litigation dispute resolution, namely court decisions have binding force. Kesimpulan penulis yaitu: Pengaturan mengenai perlindungan hukum nasabah pengguna internet banking dapat dibedakan menjadi dua yaitu perlindungan hukum preventif dan hukum represif. Peraturan perundang-undangan yang mengatur secara langsung tentang produk internet banking belum ada, namun demikian, peraturan perundang-undangan yang ada saat ini sudah mencakup aspek perlindungan hukum nasabah pengguna internet banking. Upaya hukum penyelesaian sengketa dibagi menjadi dua yaitu: Non Litigasi dan Litigasi. Non litigasi pada umunya mempunyai beberapa bentuk un-tuk menyelesaikan sengketa yaitu: Pengaduan Nasabah, Mediasi per-bankan, Badan penyelesaian sengketa konsumen (BPSK), Aribtrase dan Alternatif penyelesaian sengketa (APS), bentuk penyelesaian sengketa ini dilakukan oleh pihak yang merasa dirugikan atau ter-jadinya perbedaan pendapat baik itu antara individu, kelompok mau-pun antar badan usaha. Sedangkan penyelesaian sengketa secara liti-gasi, yakni putusan pengadilan mempunyai kekuatan mengikat.